Delay in Care Seeking for Menstrual Regulation - Sultana, Sohana; Nahar, Sabikun; Yeasmin, Sabina (Bangladesh Medical Journal, 2023)
In Bangladesh menstrual regulation (MR) services are available at all major government and private hospitals, and even at government primary health care facilities. In spite of wide availability, women who do not use menstrual regulation services from proper facilities may resort to induce unsafe abortion by non-medical or untrained health workers in unhygienic condition. Worldwide, nearly 1 in 10 pregnancies end in unsafe abortion and World Health Organization (WHO) estimates that 18 out of 20 unsafe abortions takes place in developing countries. Induced abortion leading to complication such as bleeding, infection injuries and even death, these deaths could be prevented if women had an access to safe abortion facilities. This cross sectional study was carried out among fifty two women from family planning unit of Institute of Child and Mother Health (ICMH), Dhaka from December 2009 to May 2010. The purpose of this study was to identify the factors for delay in care seeking of menstrual regulation (MR). The data were collected by using the pretested questionnaires and cases were selected from the women who came for seeking care of MR after 10 weeks of amenorrhoea. Duration of amenorrhoea was confirmed by taking history and in some cases by ultrasonography. After incorporation of the socio-demographic data; factors or reasons of delay in MR were found due to personal, social, service and family related events. The mean age of respondents was 22.14 years. About 75% of the respondents were housewives and 79% were illiterate. The mean age of marriage 19.5 years. Regarding husband’s educational level of the respondent, more than one-third (37%) was class I – V, others one-third (33%) was above the primary level rest of the husbands were higher secondary and above. More than two-third (70%) of the respondents delivered 1 to 3 live children and used oral contraceptive pills. Most of the (87%) of women gave right answer about MR and most of them (85%) had knowledge about adverse effect of MR. Nearly two-third (65%) came to know about MR form relatives/neighbors, where one-fourth (25%) from health workers and rest them from mass media/ others. Most of the (87%) respondents answered correctly about advantages of MR, however, 60% did not know about the proper time of performing MR after cessation of menstruation. Most of the respondents (85%) knew about the side effects of MR; among them more than one-third (37%) told excessive bleeding was adverse effects of MR, however 33%, 8%, 6% and rest 4% told pain, sterility, perforation and infection respectively were the adverse effects of MR. Three-fifth (60%) of the patients didn't know about the right time of pursue care for MR and 63% of them were unaware about legal aspects of MR that they have right to seek MR. More than half of the respondents (56%) stated the reasons for the delay due to their personal problem where, 19%, 15% and 10% of them were specified the reasons as social factor, service related reason and family conflict respectively. Among the respondents of personal reason for delaying MR, more than half of them (52%) took oral tablets for abortion at home, 41% failed to understand their amenorrhoea and only 7% were unaware about service facility for MR. Regarding familial reasons for delay of MR, 60% pointed out the security problem and remaining 40% told about resistance by husband/others or absence of husband in the houses. The main (70%) social reasons of delaying MR was due to spiritual bindings and 30% was due to public disgrace. Service facility related reasons for delaying MR were treatment cost (62%), distance of facility (25%) and substandard services (13%). The study findings suggested that women had good knowledge about MR even they made delay due to unawareness of their legal rights, personal issues, social and service related causes. Strengthening of reproductive health services through community clinic at community level with available awareness building program on MR may minimize the delay for care seeking of MR among women. Bangladesh Med J. 2022 May; 51(2): 37-44